Thermal Studies on Trans-Imidazolium Tetrachlorobis (Imidazole) Ruthenate(III) Dihydrate and Rhodate(III) Dihydrate - Bora, Tankeswar; K. Gogoi, Pradip; Borah, Geetika (Asian Journal of Chemistry, 2016)
Thermal studies (TG, DTG and DTA) in static air showed that trans-imidazolium tetrachlorobis(imidazole) ruthenate(III) dihydrate, (ImH)[RuCl4(Im)2]·2H2O loses two molecules of water within 200°C, followed by two steps decomposition to give unstable intermediates. At 565°C the weight loss conforms to formation of thermally reduced transient RuCl and finally there is gain in weight due to formation of nonstoichiometric oxide. Trans-imidazoliumtetrachlorobis (imidazole) rhodate(III) dihydrate becomes anhydrous around 230°C followed by two steps decomposition to several intermediates and forms spongy Rh metal at 500°C (mass loss: found 80%; calculated 78.8%) and beyond it there is weight gain due to oxide formation. The activation energies for the dehydration and two steps decomposition reactions were calculated by Freeman and Carrol’s method and the respective values for ruthenium(III) and rhodium(III) complexes were 20.1, 38.3, 153.2, 277.2 kJ mol–1 and 27.1, 76.6, 98.1 kJ mol–1. The tentative mechanism for thermal decomposition has been proposed.